A responsabilidade das operadoras de planos de saúde pelo fato do serviço prestado pelos hospitais credenciados - Pupo, Juliana Labaki (2012)
The present dissertation will present an overview about private health assistance in Brazil, having as its central theme the responsibility of Health Insurance Companies and credentialed Hospitals. It will be demonstrated the constitutional view, with the approach of the dignity principle of the human being, the main pillar of the right to health. The ways of health assistance provided by State will be discussed focusing on the activity rendered by private companies. The analysis of the context of Civil responsibility will be deepened, making a parallel between the subjective and objective responsibility, as well as a brief study on the transformation of the law in the post-modern society. Furthermore, it shall be detailed the legal nature of health insurance contracts and the applicability of the Consumer Defense Code , in which the objective responsibility by the risk of the supplier activity will prevail. The hospital activity and the extension of the health insurance companies responsibility for such services will also be discussed, considering that the hospital is chosen by the company, thus making a tripartite among ``Health Insurance Company-Hospital-Beneficiary´´. It shall be observed the sympathy among the suppliers, by demonstrating that the patient is supported by the laws of consumers protection and defense, aiming to guarantee full and effective assistance to their health